Economic Group in Labor Law: From Traditional Interpretation to Post-Reform Dynamics and 21st Century Challenges (Revista ESASP - Revista Científica Virtual da Escola Superior de Advocacia da OAB/SP, 2025)
The article explores the legal metamorphosis of the economic group institute in Brazil, starting from classic passive solidarity to the changes of Law No. 13,467/2017. The author highlights the transition from mere identity of partners to the need for proof of integrated interest and joint action (§3 of art. 2 of the CLT). The impact of the STF's intervention regarding the need for companies' participation in the knowledge phase and the challenges of ensuring the satisfaction of labor credits in the face of volatile corporate structures are discussed. (Received: June 2025 | Accepted: September 2025).
Keywords: Economic Group; Joint Liability; Labor Reform.